Sebukuh. Tribal Hut / Haritz Aiman Arman - Arman, Haritz Aiman (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The inspiration of this tribal hut is Sebukuh or knots of Kelabit’s name changing ceremony. The reason is that the Sebukuh act as tracking device that will transform into different froms based on the surroundings same goes to the concept that is conversion and the idea to convert of existing usage to a new use.